Patellar component stability improves with pulsatile lavage in total knee arthroplasty - Weiss, Ruediger J. (Springer-Verlag, 2002)
In a cadaver study, we prepared 37 fresh frozen human patella pairs to determine the efficacy of jet lavage in comparison to syringe lavage with respect to cement penetration and stability of the polyethylene patellar component after patellar resurfacing. For 12 patella pairs, sagittal sections were obtained at predefined levels using a diamond saw. Cement penetration was significantly greater (P<0.0001) in the jet lavage specimens compared to the syringe lavage specimens. For the remaining 25 patella pairs, pullout tests were performed on patellar components using a traction-compression device. The maximum force required to cause mechanical failure was significantly greater (P<0,0001) in jet lavage specimens compared to syringe lavage specimens. Our results support the routine use of jet lavage for cleansing the patellar bed prior to cement application in cemented patellar resurfacing.